2022
DOI: 10.1093/qjmed/hcac215
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of in-hospital mortality in HIV-infected patients with COVID-19

Abstract: Background Underlying immunodeficiency is associated with severe COVID-19, but the prognosis of persons with HIV (PWH) with COVID-19 is under debate. Methods Nationwide, retrospective, observational analysis of all hospitalizations with COVID-19 during year 2020 in Spain. Stratification was made according to HIV status. The National Registry of Hospital Discharges was used with the ICD-10 coding list. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
7
1
1
Order By: Relevance
“…The prevalence of bacterial coinfection and superinfection during a COVID-19 infection is different than what we have experienced with prior viral pandemics (2)(3)(4). The majority of the current studies report a low prevalence of bacterial coinfection in hospitalized COVID-19 patients, ranging from 3.1% to 8.5%.…”
contrasting
confidence: 65%
“…The prevalence of bacterial coinfection and superinfection during a COVID-19 infection is different than what we have experienced with prior viral pandemics (2)(3)(4). The majority of the current studies report a low prevalence of bacterial coinfection in hospitalized COVID-19 patients, ranging from 3.1% to 8.5%.…”
contrasting
confidence: 65%
“…In this study, microbiological tests confirmed that about 1 quarter of COVID-19 patients had a 3-fold increase in bacterial infections compared to the results of other international studies. [16,17]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, microbiological tests confirmed that about 1 quarter of COVID-19 patients had a 3-fold increase in bacterial infections compared to the results of other international studies. [16,17] A high prevalence of infection was secondary in 91% of cases, while the number of co-infections was rare. This is compatible with other studies where the prevalence was 3.5 and 14.3% for co-and secondary infections respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Baseline use of immunosuppressive medications have also been reported with an increased likelihood of secondary infection. 21 Finally, patients transferred from an outside facility were likely due to more severe COVID-19 because our institution serves as a referral center for the state of Oregon.…”
Section: Discussionmentioning
confidence: 99%